Effect of Position Analysis and Competence on Employee Performance at BPR Prima Sejahtera - Hermawan, Rangga Adhitia; Rahayu, Endah Sri; Pajar (International Journal of Economics, Management and Accounting (IJEMA), 2025)
Job analysis and employee competence carried out in accordance with the placement will have a positive impact on the organisation, and the wrong one will have a negative impact. For example, among others, it results in the emergence of unrest in the environment of the employees concerned, decreased morale and work passion which of course will be able to reduce employee productivity and work performance.This study uses cross-sectional quantitative research techniques. To find out how the influence between the variables of Position Analysis and Competence on employee performance. by giving questionnaires to employees totalling 34 employees. sampling techniques in this study using saturated samples, namely the entire population is used as a sample because the population is less than 100 people. position analysis has no effect on employee performance. competence affects employee performance. position analysis and competence simultaneously affect employee performance. the conclusion of this study is that the position analysis variable has no effect on employee performance, it is hoped that in the future the company can further optimise position analysis in improving employee performance. competency variables affect employee performance, it is hoped that in the future the company can improve employee competence in order to improve its performance.